Cochrane Database of Systematic Reviews 2006
DOI: 10.1002/14651858.cd006109
|View full text |Cite
|
Sign up to set email alerts
|

Oral contraceptive pill, progestogen or estrogen pre-treatment for ovarian stimulation protocols for women undergoing assisted reproductive techniques

Abstract: Background For many subfertile women, assisted reproductive techniques (ART) is the only hope for a pregnancy and live birth. The combined oral contraceptive pill (OCP) given prior to the hormone therapy in an IVF cycle may result in better pregnancy outcomes of ART. Objectives To assess whether pre-treatment with combined OCPs, progestogens or estrogens in ovarian stimulation protocols affects outcomes in subfertile couples undergoing ART. Search methods We searched the Cochrane Menstrual Disorders and Subfer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 29 publications
0
14
0
2
Order By: Relevance
“…A meta-analysis showed in GnRH agonist cycles that progestin pretreatment was associated with higher clinical pregnancy rate than placebo or no pretreatment (Smulders et al, 2010). Our results showed that progestin-induced menses was associated with higher levels of estradiol and LH and comparable endometrial thickness on the day of hCG trigger than spontaneous menses.…”
Section: Discussionmentioning
confidence: 50%
See 1 more Smart Citation
“…A meta-analysis showed in GnRH agonist cycles that progestin pretreatment was associated with higher clinical pregnancy rate than placebo or no pretreatment (Smulders et al, 2010). Our results showed that progestin-induced menses was associated with higher levels of estradiol and LH and comparable endometrial thickness on the day of hCG trigger than spontaneous menses.…”
Section: Discussionmentioning
confidence: 50%
“…However, the effects of OCs or progestins pretreatment on outcome of IVF cycle remain inconclusive (Smulders et al, 2010), especially in PCOS which was often an exclusion criterion in many previous randomized trials investigating such effects (Cedrin-Durnerin et al, 2007;Huirne et al, 2006;Kolibianakis et al, 2006;Rombauts et al, 2006). OCs used for cycle scheduling in women with regular menses were suggested to have a remnant adverse effect on outcomes after fresh embryo transfer (Griesinger et al, 2010;Smulders et al, 2010). Frozen embryo transfer (FET) has been increasingly used and an elective freeze-all strategy has recently been advocated (Shapiro et al, 2014;Weinerman and Mainigi, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, a Cochrane review evaluating the use of oral contraceptives in ovarian stimulation protocols reported lower clinical pregnancy rates, a longer duration of stimulation, and higher gonadotropin consumption with OCP pretreatment in GnRH antagonist cycles. However, the authors acknowledged that most of the studies included in the review were small and of poor quality [28]. A meta-analysis of 6 randomized controlled trials also reported significantly lower ongoing pregnancy rates in GnRH antagonist cycles utilizing OCP pretreatment compared with antagonist cycles without pretreatment (-5% difference) [22].…”
Section: Discussionmentioning
confidence: 99%
“…33 OK kullanılan grupta elde edilen oosit sayısı ise daha yüksek bulunmuştur. 34 Bu veriler OK'ların GnRH antagonistleriyle olumsuz etkileşimi olduğunu göstermektedir. OK eklenmesiyle gebelik oranlarındaki düşmenin nedeni ise net değildir.…”
Section: şEki̇l 1: Standart Long Protokolunclassified